Immunohistochemical analysis of lichenoid reactions in patients treated with anti‐PD‐L1 and anti‐PD‐1 therapy. (10th February 2016) - Schaberg, Kurt B.; Novoa, Roberto A.; Wakelee, Heather A.; Kim, Jinah; Cheung, Christine; Srinivas, Sandhya; Kwong, Bernice Y.
Abstract : Background: Recent advances in the immunotherapeutic treatment of cancer have led to the development of multiple new directed therapies including monoclonal antibodies that block the immune checkpoint T‐cell receptor programmed death 1 (PD‐1) and the PD‐1 ligand, programmed death ligand 1 (PD‐L1). Various immune‐related toxicities have been associated with these drugs including, most commonly, skin rashes. Methods: Five cases of lichenoid dermatitis, including one case of lichenoid mucositis and one case of lichen sclerosus, associated with anti‐PD‐L1 and anti‐PD1 therapy were compared with three biopsies of non‐drug‐related lichen planus (LP) and three lichen planus‐like keratoses (LPLK) used as controls. Results: Histopathologic and immunophenotypic analysis of these lichenoid lesions demonstrated significantly greater histiocytic infiltrates than observed in control lichenoid reactions (p = 0.0134). We also observed increased spongiosis and epidermal necrosis. No significant differences were seen in expression of CD3, CD4:CD8, CD20, PD‐1, CD25, Foxp3, CXCL13 and PD‐L1 expression. Conclusions: These findings expand the literature of immune‐related toxicities of PD‐L1 and PD‐1 blockade to include lichenoid dermatitis and lichenoid mucositis. Of note, these cutaneous side effects were amenable to topical treatment, without the need for medication dose reduction or discontinuation.